2013
DOI: 10.3748/wjg.v19.i10.1582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Rh2 on growth and migration of pancreatic cancer cells

Abstract: Ginsenoside Rh2 inhibits proliferation, migration and invasion and induces apoptosis of the human pancreatic cancer cell line Bxpc-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…30) GRh2 and GRg3 have been shown to have potent ability in inhibiting growth of different strains of tumor cells and to cause distinctive morphological changes. [31][32][33] It was reported that after 24 h of treatment with GRg3 (10 µM) and GRh2 (10 µM), hepatoma cells clearly exhibited condensed and fragmented nuclei, indicative of apoptotic cell death. 15) In this report, we observed that increasing concentration of 20(S)-GRh2 induced a marked increase in condensed apoptotic nuclei (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…30) GRh2 and GRg3 have been shown to have potent ability in inhibiting growth of different strains of tumor cells and to cause distinctive morphological changes. [31][32][33] It was reported that after 24 h of treatment with GRg3 (10 µM) and GRh2 (10 µM), hepatoma cells clearly exhibited condensed and fragmented nuclei, indicative of apoptotic cell death. 15) In this report, we observed that increasing concentration of 20(S)-GRh2 induced a marked increase in condensed apoptotic nuclei (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that G-Rh2 could inhibit proliferation, invasion and metastasis of multiple human cancers. 24,25) Inducing apoptosis in cancer cells is an important mechanism of many anti-cancer agents in impairing malignant proliferation. It was believed that G-Rh2 is one of the multitarget anti-cancer drugs which could induce apoptosis of cancer cells by canonical signaling pathways, namely the death receptor-dependent and mitochondrial apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has proved that these rare ginsenosides show relatively strong activities on anticancer. For example, ginsenosides Rh 2 can against human pancreatic, Colorectal, leukemia cancer cells Tang et al, 2013;Chung et al, 2013); ginsenosides Rg 3 can against human prostate, colon, breast, gastric cancer cells (Sun et al, 2010;Yuan et al, 2010;Chen et al, 2011;Kim et al, 2011;Pan et al, 2012); ginsenosides F 2 can against glioblastoma, breast cancer cells (Ji et al, 2012;Trang et al, 2012); ginsenosides compound K can against human lung adenocarcinoma, hepatoma, colorectal cancer cells Li et al, 2013) . Hence, these rare ginsenosides would develop into excellent anticancer drugs.…”
Section: Ginsenosidesmentioning
confidence: 99%